1988
DOI: 10.1037/0097-7403.14.2.131
|View full text |Cite
|
Sign up to set email alerts
|

Representation of serial order in monkeys (Cebus apella).

Abstract: Cebus monkeys were trained on a five-item serial learning task, symbolized as ABCDE; the initial stages of training were on the shorter subseries AB, ABC, and ABCD. To assess the monkeys' knowledge of the sequential position of each item, pair-wise tests were given to 2 subjects after acquisition of the ABCD series and to 4 subjects after reaching criterion on the ABCDE series. In both tests, the monkeys performed at high levels on the interior pairs, which were BC for the ABCD series, and BC, BD, and CD for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
193
1
3

Year Published

1996
1996
2020
2020

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 147 publications
(212 citation statements)
references
References 17 publications
15
193
1
3
Order By: Relevance
“…Concern with position learning in animals has, however, found voices that reflect the contemporary cognitive orientation (e.g., D 'Amato, 1991;D'Amato & Colombo, 1988;Roitblat et aI., 1983). Encouraged by apparent comparative differences in associative transitivity experiments, D' Amato and his colleagues (reviewed in D ' Amato, 1991) have proposed that, in monkeys (Cebus apella), a lucid internal representation of the series elements and their positions is formed, and the animal accesses this representation and scans it from initial to final positions.…”
Section: Discussionmentioning
confidence: 99%
“…Concern with position learning in animals has, however, found voices that reflect the contemporary cognitive orientation (e.g., D 'Amato, 1991;D'Amato & Colombo, 1988;Roitblat et aI., 1983). Encouraged by apparent comparative differences in associative transitivity experiments, D' Amato and his colleagues (reviewed in D ' Amato, 1991) have proposed that, in monkeys (Cebus apella), a lucid internal representation of the series elements and their positions is formed, and the animal accesses this representation and scans it from initial to final positions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous experiments have shown that monkeys acquire knowledge of the ordinal position of list items following training on a single 5-item list (D'Amato & Colombo, 1988) or training on multiple lists containing 3 or 4 items (Chen, Swartz, & Terrace, 1997;Orlov, Yakovlev, Hochstein, & Zohary, 2000). In the present experiment, knowledge of ordinal position was evaluated by a 2-item-subset test that was derived from all 28 of the photographs used to construct the four 7-item lists.…”
Section: Evaluating Knowledge Of Ordinal Position Of List Itemsmentioning
confidence: 99%
“…Thus chunking is viewed as mediated through a higher order cognitive process that reduces the actual load of working memory. The evidence on the facilitation of both acquisition and performance suggests that subjects are 'seeking' for a rule based organization of a serial task, be it in sequence discrimination, sequence production or stimulus tracking paradigms (Hulse 1978, D'Amato and Colombo 1988, Dallal and Meck 1990, Fountain and Annau 1990, Terrace 1991. During song learning the success of pattern acquisition seems not to be based on such rule based coding: subjects did not imitate more songs from the strings which they had chunked according to experimental structure than from the string where cueing was not successful (experiment III).…”
Section: Discussionmentioning
confidence: 99%